The Portrait of Feminism in the Pop Song Lyrics of the "Millennial Generation" Era in the Songs of Male Singers - Widiyanti, Diya Sri (SCHOLASTICA: Jurnal Pendidikan dan Kebudayaan, 2022)
The depiction of the new female figure in the post-modern era is very influential in current developments. The figure of a woman no longer exists in the patriarchal system which must be subordinate to men. Women are depicted as independent figures and free to determine their choices in living their lives. The depiction of women's freedom, or what is better known as post feminism, is also depicted in several songs in the 2000s which were popularized by several male singers, including: The song won't disappear by Budi Doremi 2022, the song Be Careful on the Road, Sincere (2022) and virgoun when my heart asks (2022). The method used in this research is descriptive qualitative where the researcher goes directly to analyze the results of the work designated as the research object. The theory used in this research is post-feminism theory and also discourse analysis which was popularized by Van Djik. The results obtained by this research are women's equality in relationships with men and also girl power in post modernism. So based on the findings, it is known that women have an important role in current developments.